Improvement of decal transfer method for preparing fast and reliable CCM assembly - Hurtig, Adam (My University, 2024)
As sustainable energy solutions have garnered more importance in society and to governmental bodies, a technology getting attention as being part of the solution and a step in the right direction is the proton exchange membrane fuel cell (PEMFC). This comes as the PEMFC uses hydrogen and oxygen to create electricity, with the side-products being heat and water, which means that it is a very clean energy converter. At the heart of the fuel cell is the catalyst coated membrane (CCM), which is where the reactions take place, and it is the component investigated in this thesis. Although there are multiple ways of fabricating CCMs, the method used in this thesis is the decal transfer method. Using this method, parameters such as temperature and pressure were varied to investigate the optimal parameters under different conditions. These conditions included the usage of different membranes, three different cathode loadings and two CCM areas. During this process, several analytical tools were employed, with the intent of finding the most effective quality check method for in-house production of CCMs. This included the usage of an optical microscope, lightboard and high intensity light. The performance of CCMs assembled using optimized parameters was also examined by in-situ fuel cell testing. Lastly, an investigation into the most appropriate pressure pad material was performed. The results in this thesis outlines the optimal parameters for each condition and proposes both the most effective quality check method and the most suitable pressure pad material.
Keywords: proton exchange membrane fuel cell; catalyst coated membrane; decal transfer